Molecular identification of Ryadg , Rychc and Rysto resistance genes to potato virus Y in potato collection samples - Kyrychenko, S.; Borzykh, О.; Bondus, R.; Sozinov, I.; Mishchenko, L.; Kozub, N. (Quarantine and plant protection, 2025)
Goal. Screening of a collection of potato varieties using the polymerase chain reaction (PCR) method for the presence of three genes that provide extreme resistance (ER) to Potato virus Y (PVY) namely Ryadg , Rychc and Rysto. Methods. DNA was extracted from the leaves or tubers of potato varieties of Ukrainian and foreign origin using a silica-based method. The following primers were used to identify the genes: RY1648F24/R22 for the gene Rychc, YES3-A for the Rysto gene, and RYSC3 for Ryadg. The amplified products were analyzed by agarose gel electrophoresis. Results. Ukrainian varieties were studied for the first time using the direct molecular marker RY1648F24/R22. Sixty-eight samples of different origins were analyzed for this molecular marker of the Rychc gene, and the gene of interest was identified in 11 varieties. Using the YES3-A molecular marker, 34 potato samples were evaluated and the Rysto gene marker amplicon was detected in 5 samples. Among the 58 potato varieties analyzed, the Ryadg gene was detected by the RYSC3 marker only in the Resurs variety, which also had the Rysto gene marker. Conclusions. The presence of genes of extreme resistance to PVY, Ryadg , Rychc , and Rysto was detected in 16 Ukrainian and foreign potato varieties. The Resurs variety has a combination of Ryadg and Rysto genes. The varietis carrying the ER genes identified during the study as carriers of genes for extreme resistance to PVY can be used in the breeding process.